Improving falls in nursing homes: a post-fall huddle quality improvement project - Buckner, Tekekee; Sherry, Daisy (International Journal of Advanced Nursing Studies, 2019)
Falls are one of the most common preventable health problems in adults 65 years and older (AHRQ, 2013). A fall in this population can have a devastating effect often leading to a significant change in morbidity or death. Adults in assisting living, nursing homes, and skilled facilities (SNF) have an increased risk of falling and having a subsequent fall due to an acute illness, weakness, or confusion. This makes individualizing a plan of care to prevent a secondary fall and identifying the root cause of falls within a facility imperative.In our agency, the fall rate is nearly triple that of the national benchmark. To address this problem, a Post-Fall Huddle project was implemented. The literature recommends and supports the practice of a post-fall assessment program in fall reduction to identify intrinsic and extrinsic fall risk etiologies. There was found to be a reduction in the absolute values of recurrent patient falls per quarterly reporting after the implementation of the post-fall huddle. The results also provided pertinent data that can be used for recommendations in future fall prevention for the SNFÂ